Music within everyone’s reach: a transdisciplinary experience of expression and artistic co-creation as a way to combat the stigma of mental illness - Caspurro, Helena (2023)
Music and the arts have played a significant role in addressing social exclusion, particularly through what is defined as community art or participatory arts practices. The present study, in line with this philosophy and also with the artistic research or practice-based research, focuses on the stigma of mental illness and seeks to contribute to the development of literacy around this form of exclusion. It is associated to the project Paluí, está aqui? Histórias sonoras para cantos interiores (which is one of the several transdisciplinary studies, derived from the original musical work Paluí, developed by teachers and researchers of University of Aveiro) and aimed at: 1) the invention and conception of a musical and transdisciplinary show that, from an artistic and social point of view, would enable the construction, among all participants, of a common cultural project based on experiences of collaborative, performative, expressive and aesthetic involvement, in a dynamic of collective and inclusive creation and artistic interpretation; 2) the musical study of Paluí, the original work, and forms of scenic treatment, with a view to its: i) creative transformation into a unique artistic show; ii) possibility to be built, performed and created by all; iii) capacity to agglutinate, in a coherent whole, areas such as Drama, Dance, Video and Handicrafts. Music students, teachers and researchers of music, design and visual arts from Department of Communication and Art of University of Aveiro, Polytechnic Institut of Porto, a musician from Casa da Música, a group of children from a school of Aveiro (CIAQ) and users and patients from the Magalhães Lemos Hospital (Porto), a total of 129 elements, participated in the creation and realization of the show, which was presented at Ao Alcance de Todos festival, at Casa da Música (Porto), in 2019. The artistic results, materialized in improvisations and compositions of sound/music, drama, choreography, videography, scenic scripts, artifacts and instruments, interpretations and performances are realized and demonstrated throughout the collective process (about 6 months) and, especially, in two concerts recorded and published in two films (2020). Since the stigma of mental illness is a dimension and a perception of social exclusion, what is artistically realized by all participants, and the way how they achieved, also suggests interpreting the experience performed as a path of social construction and inclusion through musical and transdisciplinary imagination. Experiences like these, despite not being sufficient to eliminate or extinguish the stigma of mental illness, especially in the long term, seem to enable environments that are particularly significant and conducive to the construction of identity among people where positive and inclusive perceptions and attitudes also germinate. Thinking about the broader social meaning: even as a small contribution to the development of literacy in mental illness, what we managed to experience, feel and achieve allows us to reinforce that music and the arts, when governed by humanist values and social purposes, can constitute effective and meaningful paths for the construction of more inclusive, just, wise, creative and democratic societies.